Kandungan Gizi Tanaman Maman (Cleome Gynandra L) dan Joruk Maman - Lily Lily Restusari; Sri Mulyani; Yuliana Arsil; Fathul Jannah (LPPM Universitas Abdurrab, 2023)
Maman (Cleome gynandra L) is one of the plants that is often consumed by people in Riau Province, especially in Rokan Hulu and Rokan Hilir Regencies. Maman is usually consumed in a fermented form called joruk maman. The nutritional value content of a food ingredient can be known through several analyses, one of which is proximate analysis. Based on the background stated above, it is necessary to conduct research to determine the nutritional content of protein, fat, fiber, carbohydrates, water content and ash content of maman plants, fresh and dried (simplesia), and Joruk Maman. The types and methods used in this research are experimental research and quantitative descriptive methods. The results of proximate analysis on three samples showed that the highest levels of protein in maman powder (30.08%), fat content in joruk maman (2.95%), water content in joruk maman (92.06%), carbohydrate content in maman powder (26.9727%), ash content in maman powder (17.75%), and fiber content in maman powder (7.84%).